Validation of viscoelastic coagulation tests during cardiopulmonary bypass. (26th May 2015) - Ortmann, E.; Rubino, A.; Altemimi, B.; Collier, T.; Besser, M. W.; Klein, A. A.
Summary Background Viscoelastic point‐of‐care tests such as thromboelastography (TEG) and rotational thromboelastometry (ROTEM) are increasingly used to guide hemostatic therapy after cardiac surgery. The aim of this study was to assess their clinical utility during cardiopulmonary bypass to predict postbypass coagulation status and to guide therapy. Methods In this prospective study, TEG and ROTEM tests were performed in 52 adult patients undergoing elective cardiac surgery at two time points: near the end of cardiopulmonary bypass and after heparin reversal with protamine. The 95% confidence intervals of the mean difference were compared with a prespecified clinically relevant limit of ± 20% of the value after protamine. Results Both viscoelastic fibrinogen assays were well within the prespecified clinically relevant limit (≥ 79% of patients). The laboratory Clauss fibrinogen was much lower during cardiopulmonary bypass than after protamine (mean difference 1.2 g L−1, 95% CI 1.03–1.4, which was outside a clinically acceptable difference. For intrinsically activated tests, clotting times (CT) were different and outside the prespecified limit on TEG (mean difference ‐1.2 min, 95% CI ‐1.8 to ‐0.6) but not on ROTEM (mean difference 2.3 sec, 95% CI −8.6 to 13.2), while clot strength was well within the clinical limit on both devices (≥ 94% of patients). For extrinsically activated tests, clot strength on both TEG and ROTEM was within the pre‐specified limit in 98% of patients. Conclusions Results from TEG and ROTEM tests performed toward the end of cardiopulmonary bypass are similar to results after reversal of heparin. Amplitudes indicating clot strength were the most stable parameters across all tests, whereas CT showed more variability. In contrast, laboratory testing of fibrinogen using the Clauss assay was essentially invalid during cardiopulmonary bypass.